1990
DOI: 10.1021/jm00173a031
|View full text |Cite
|
Sign up to set email alerts
|

Potent anticonflict activity and lessening of memory impairment with a series of novel [1]benzothieno[2,3-c]pyridines and 1,2,3,4-tetrahydro[1]benzothieno[2,3-c]pyridines

Abstract: [1]Benzothieno[2,3-c]pyridines (10a-c, 11, 12a-t, and 13a,b) and 1,2,3,4-tetrahydro[1]benzothieno[2,3-c]pyridines (3a-c, 7, 8a-c, and 9) were synthesized. The compounds are bioisosteres of beta-carbolines and 1,2,3,4-tetrahydro-beta-carbolines where the indole nitrogen is replaced by sulfur. Their pharmacological activity was evaluated in a water lick conflict test in rats and a passive avoidance test in mice. In the 1,2,3,4-tetrahydro[1]benzothieno[2,3-c]pyridine series, the presence of ethyl ester (3b) or cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…To this end, γ-hydroxy thienyl oxime 1c was chosen as a starting point for the preparation of diverse enantioenriched building blocks (Scheme A). The rhodium-catalyzed and oxime-directed C–H activation of enantioenriched ( S )- 1c furnished thienopyridine 4 , a promising motif in drug discovery, without any erosion of the optical purity. The lithiation of dihydrooxazine 3c and subsequent trapping with allyl bromide allowed the selective installation of an additional stereocenter ( 5 ), showcasing the applicability of the method for the synthesis of highly substituted heterocycles.…”
mentioning
confidence: 99%
“…To this end, γ-hydroxy thienyl oxime 1c was chosen as a starting point for the preparation of diverse enantioenriched building blocks (Scheme A). The rhodium-catalyzed and oxime-directed C–H activation of enantioenriched ( S )- 1c furnished thienopyridine 4 , a promising motif in drug discovery, without any erosion of the optical purity. The lithiation of dihydrooxazine 3c and subsequent trapping with allyl bromide allowed the selective installation of an additional stereocenter ( 5 ), showcasing the applicability of the method for the synthesis of highly substituted heterocycles.…”
mentioning
confidence: 99%
“…Heteroaryl amides are both useful synthetic intermediates and important structural elements of several drugs and candidates, including the hypnotic agent rilmazafone and the HIV non-nucleoside reverse transcriptase inhibitor delavirdine (Figure ). , We have previously demonstrated that N,N-disubstituted aminoacetonitrile derivatives ( 1 ) are effective synthons of the corresponding amides 2 via a procedure that takes advantage of umpolung-like properties of 1 , as summarized in Figure . The anion of 1 , prepared by deprotonation using NaHDMS in THF, was reacted with an ester 3 to provide intermediate 4 (Scheme ).…”
mentioning
confidence: 99%